Deletion of 3p13-14 locus spanning FOXP1 to SHQ1 cooperates with PTEN loss in prostate oncogenesis - Hieronymus, Haley (Nat Commun, 2017)
A multigenic locus at 3p13-14, spanning FOXP1 to SHQ1, is commonly deleted in prostate cancer and lost broadly in a range of cancers but has unknown significance to oncogenesis or prognosis. Here, we report that FOXP1-SHQ1 deletion cooperates with PTEN loss to accelerate prostate oncogenesis and that loss of component genes correlates with prostate, breast, and head and neck cancer recurrence. We demonstrate that Foxp1-Shq1 deletion accelerates prostate tumorigenesis in mice in combination with Pten loss, consistent with the association of FOXP1-SHQ1 and PTEN loss observed in human cancers. Tumors with combined Foxp1-Shq1 and Pten deletion show increased proliferation and anaplastic dedifferentiation, as well as mTORC1 hyperactivation with reduced Akt phosphorylation. Foxp1-Shq1 deletion restores expression of AR target genes repressed in tumors with Pten loss, circumventing PI3K-mediated repression of the androgen axis. Moreover, FOXP1-SHQ1 deletion has prognostic relevance, with cancer recurrence associated with combined loss of PTEN and FOXP1-SHQ1 genes.